Investigating Interdisciplinary Collaboration - Frickel, Scott (Rutgers University Press, 2021)
Interdisciplinarity has become a buzzword in academia, as research universities funnel their financial resources toward collaborations between faculty in different disciplines. In theory, interdisciplinary collaboration breaks down artificial divisions between different departments, allowing more innovative and sophisticated research to flourish. But does it actually work this way in practice?